Fostering critical thinking through peer review between cooperative learning groups (Revista Lusófona de Educação, 2016)
Educational policies keep stressing the importance of critical thinking skills for promotion of academic success in Higher Education, to facilitate transition into the labour market and to foster livelong learning. Curricula in Higher Education Institutions gradually meet this necessity, integrating strategies foreseeing the development of critical thought in students. However, at this level, we still commonly found teaching and learning strategies emphasizing a more or less passive knowledge transfer, focusing on the student’s ability to memorize in- formation. Peer review and feedback, allied to cooperative work, are important components of active learning and development of critical thinking skills pro- cess. It is therefore important to understand the role and influence of feedback provision in peer review activities between cooperative groups. This study analyses the perceptions and attitudes of 27 students in two Masters Courses on the feedback given in peer review activities (between groups), based on their responses to a survey. Results showed, among other aspects, that collaborative work and feedback exchange between groups fostered the contact with different perspectives towards the same situation, and that its critical analysis allowed the students to enhance different skills, the most referred one being the critical thinking. Keywords: critical thinking; cooperative learning; peer review.